Biological effects of desert dust in respiratory epithelial cells and a murine model. (April 2014) - Ghio, Andrew J.; Kummarapurugu, Suryanaren T.; Tong, Haiyan; Soukup, Joleen M.; Dailey, Lisa A.; Boykin, Elizabeth; Ian Gilmour, M.; Ingram, Peter; Roggli, Victor L.; Goldstein, Harland L.; Reynolds, Richard L.
Abstract As a result of the challenge of recent dust storms to public health, we tested the postulate that desert dust collected in the southwestern United States imparts a biological effect in respiratory epithelial cells and an animal model. Two samples of surface sediment were collected from separate dust sources in northeastern Arizona. Analysis of the PM20 fraction demonstrated that the majority of both dust samples were quartz and clay minerals (total SiO2 of 52 and 57%). Using respiratory epithelial and monocytic cell lines, the two desert dusts increased oxidant generation, measured by Amplex Red fluorescence, along with carbon black (a control particle), silica, and NIST 1649 (an ambient air pollution particle). Cell oxidant generation was greatest following exposures to silica and the desert dusts. Similarly, changes in RNA for superoxide dismutase-1, heme oxygenase-1, and cyclooxygenase-2 were also greatest after silica and the desert dusts supporting an oxidative stress after cell exposure. Silica, desert dusts, and the ambient air pollution particle NIST 1649 demonstrated a capacity to activate the p38 and ERK1/2 pathways and release pro-inflammatory mediators. Mice, instilled with the same particles, showed the greatest lavage concentrations of pro-inflammatory mediators, neutrophils, and lung injury following silica and desert dusts. We conclude that, comparable to other particles, desert dusts have a capacity to (1) influence oxidative stress and release of pro-inflammatory mediators in respiratory epithelial cells and (2) provoke an inflammatory injury in the lower respiratory tract of an animal model. The biological effects of desert dusts approximated those of silica.